Primary non-Hodgkin’s lymphoma of the talus: case report - Marconato, Gianfrancesco; Silva, Joao Luiz Vieira; Costa, Renan Marson; Moura, Márcio Fernando Aparecido de (Scientific Journal of the Foot & Ankle, 2019)
Lymphoma is a blood cancer that begins in different types of lymphoid or histiocytic cells in various states of maturity. Primary lymphoma of bone is rare, and clinical manifestations include localized pain and edema. The diagnosis takes into consideration the clinical picture, imaging tests and pathological anatomy. In this article, we present the case of a patient with restricted daily activities and loss of quality of life due to primary non-Hodgkin’s lymphoma of the talus. After chemotherapy, the clinical condition of the patient improved. Level of Evidence V; Expert Opinion.